Learning Reading Skills Based on Local Wisdom - Mohammad Zainal Hamdy; Wiwik Prasetiyo Ningsih (Aqlamuna: Journal of Educational Studies, 2024)
Arabic language learning will always face various challenges in accordance with the development of the times. Teachers will always be required to make learning interesting and have an influence on students, especially in moral changes. Therefore, the main objective of this study is to integrate local wisdom into Reading skills learning so that students not only master Arabic but also understand and appreciate local culture so that they can increase students' interest and competence in reading Arabic and strengthen their cultural identity and character. This study uses a Qualitative Approach with the Ethnomethodology Method where data is collected using Documents and Observations and using Componential data analysis. The results of this study indicate that local wisdom-based maharah qira'ah learning is very important to improve students' reading skills and strengthen their cultural identity. Integrating local wisdom into education has a positive impact on the development of students' interests and competencies. In addition, local wisdom will also create and foster a sense of love for Indonesia, especially their own region, in each student by recognizing the diversity of wealth possessed by the Indonesian nation